Exploring the correlates and nature of subjective anomalous interactions with objects (psychometry): a mixed methods survey - Christine A. Simmonds-Moore (Frontiers in Psychology, 2024)
IntroductionPsychometry refers to the experience of receiving information about a person or thing by contact with a given object. There is little research to date on the psychological correlates of psychometry and no systematic qualitative research on the nature of the experience itself.MethodA convergent mixed methods online survey sought to explore how synesthesia and autonomous sensory meridian response (ASMR) correlate with a range of anomalous experiences, including psychometry, among members of the public. Those who reported that they had experienced psychometry were invited to describe their experiences in an open ended section.ResultsResults indicate that those who experience psychometry scored higher on a measure of ASMR than those who did not. Those who experience synesthesia also scored significantly higher on a measure of ASMR than those who did not. However, synesthesia was not significantly associated with psychometry. Both ASMR and synesthesia were associated with tendencies to report anomalous experiences (with and without a paranormal attribution). A thematic analysis found five themes including: a flash of imagery; lived feelings and intense emotions; noesis and perspective taking/empathy. Subjective psychometry experiences seem to reflect emotional information that is experienced as different to one’s normal experiences and felt to be from the perspective of another person.DiscussionResults are discussed and quantitative and qualitative findings are integrated.